Teacher performance assessment system training at SMK Negeri 7 Samarinda - Damar Nurcahyono; Farindika Metandi; Abdul Najib (Community Empowerment, 2021)
This Community Service (PkM) activity aims to assist the teachers and Principals of SMK Negeri 7 Kota Samarinda in using the teacher performance appraisal system developed by the PkM Team of the Samarinda State Polytechnic (Polnes). Through the system, performance information can be shortened and more accurate. This system is expected to help teachers and principals to improve school performance to be more efficient and effective. This service is carried out in four stages, the first is the observation stage to identify the problems faced by teachers and school principals. The second is the socialization stage to provide an understanding of the importance of digitalization in school management. The third is the design of an application-based teacher performance appraisal system and the last is training in the use of teacher performance appraisal applications. The results of the service show that teachers can understand the importance of digitalization in school management and are able to operate teacher performance appraisal applications skillfully.